Safety of apremilast: risk of psychical disorders - T. M. Bukatina; N. Yu. Velts; M. A. Darmostukova; E. Yu. Pasternak; T. V. Romanova (Безопасность и риск фармакотерапии, 2018)
Apremilast is a new selective inhibitor of phosphodiesterase 4 (PDE4) of the class of small molecules, approved for treatment of psoriatic arthritis and psoriasis. The efficacy and safety of apremilast in the treatment of moderate to severe plaque psoriasis have been demonstrated in multicenter, randomized, double-blind, placebo-controlled clinical trials of ESTEEM 1 and ESTEEM 2 (Efficacy and Safety Trial Evaluating the Effects of Apremilast in Psoriasis). These studies describe adverse reactions such as mental disorders: depression, suicidal thoughts, suicidal behavior. However, data on the increase in the incidence of these adverse reactions during longer treatment with apremilast were not obtained. The article presents the reports from the UK regulator (MHRA) and international database VigiBase on the increased risk of developing suicidal thoughts, suicide attempts, completed suicides and suicidal behavior during treatment with apremilast.